Asociación de las características de árboles atacados por la avispa de los pinos Sirex noctilio y el parasitismo del nematodo Deladenus siricidicola en la provincia de Neuquén = Association of the characteristics of trees attacked by the woodwasp Sirex noctilio and the parasitism of the nematode Deladenus siricidicola in the Neuquén province - Venticinque, Natalia Aldana (2019)
The nematode Deladenus siricidicola parasitizes Sirex noctilio female wasps, making them sterile. The association between physiological and morphological characteristics of the host, Pinus sp, with a higher parasitism, in order to guide the selection of trees that should preferably be inoculated with the nematode about other trees, registered significant differences for the DAP and the shape of the stem. It wasn´t observed differences for trees inoculated and control. The combination of variables in a tree with a higher probability of obtaining a parasitism higher than 18% is: semi-dry or dry foliage, DBH between 25-30.1 cm, stratum suppressed and straight stem.